Analysis of National Land Board Authority on Land Dispute Which have not been Registered in The Land Office of Samarinda - Robyatul Adawiyah; Hadi Noor Cahyo; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
According to Article 3 letter f Presidential Regulation No. 20 of 2015 stipulates that the National Land Agency performs functions include formulation and implementation of policies in the field of control and the handling of disputes and case land. Most of land that has not been registered in BPN Samarinda because of several problems, one status each land dispute. The purpose of this study was to analyze the authority BPN Samarinda on disputed land which has not been registered and analyzing obstacles and solutions. Metode approach used in this study is a sociological juridical approach. Mechanical collection of legal materials in this study is by interview and literature study techniques, data analysis techniquesdescriptive analytic method is used.The results showed that the Authority granted to BPN in resolving land disputes is procedurally done by first conducting studies and approaches to the parties to the dispute, namely through consultation and the courts / litigation.Barriers BPN authority over land disputes that have not been registered at the BPN Samarinda is the lack of public knowledge about the land, the lack of public awareness and public access to information and services is still minimal, most people live in rural surroundings with facilities and means of transport and communications are limited. BPN solutions that can be done is through deliberative approach, but if consensus is not reached, it will be taken by the courts / litigation. Also BPN proactive approach with mobile services from village to directly deal with the public in the form of activities, socialization, education, land registration, measurement and delivery of certificates.Keywords: BPN Authority; Land Registry; Land Dispute.